Prevention of mood disorder after stroke: a randomised controlled trial of problem solving therapy versus volunteer support - Kate Hill; Allan House; Peter Knapp; Carrie Wardhaugh; John Bamford; Andy Vail (BMC Neurology, 2019)
Abstract Background Mood disorder after stroke is common but drug and psychosocial treatments have been assessed with disappointing results. Preventing mood disorder from developing in the first place could be a better approach and might reduce the need for pharmacotherapy in this predominantly older patient group. We used a brief problem-solving therapy and evaluated its effect in reducing mood disorder in the 12 months after stroke. Methods A 3-group, parallel, randomised controlled trial. Four hundred fifty patients with stroke were randomised within 1 month of hospital admission to problem-solving therapy from a psychiatric nurse, non-specific support given by volunteers or treatment-as-usual. Follow up took place at 6 and 12 months after stroke. Standardised measures of mood (Present State Examination, GHQ-28), cognitive state (mini-mental state examination) and function (Barthel ADL index, Frenchay Activities Index) were taken at baseline, 6 and 12 months after randomisation. Satisfaction with care was recorded at follow up. Results At 6 months, all psychological and activity measures favoured problem-solving therapy. At 12 months, patients in the problem-solving therapy group had significantly lower GHQ-28 scores and lower median Present State Examination symptom scores. There were no statistically significant differences in activity. The problem-solving therapy group were more satisfied with some aspects of care. Conclusions The results are encouraging and suggest it is possible to prevent mood disorder in stroke patients using a psychological intervention. The differences between the groups at 12 months may indicate a sustained impact of psychological therapies, by comparison with non-specific support. Trial registration ISRCTN: ISRCTN33773710 Registered: 23/01/2004 (Retrospectively).